Resource Allocation Method for 5G Communication System Based on ICHOA - Hou, Huanpeng; Lu, Jizhao; Li, Yongjie; Qi, Xiaoyong; Wei, Xiangxin (2024 4th International Conference on Neural Networks, Information and Communication (NNICE), 2024)
With the advancement of the commercial process of the fifth generation (5G) mobile communication systems, device to device (D2D) communication has attracted more and more attention. In order to solve the problems of high computational complexity and poor allocation optimization effect of existing 5G communication system resource allocation algorithms. This article proposes a resource allocation optimization method for 5G network D2D communication system based on the improved Chimp Optimization Algorithm (ICHOA). It introduces hunting contribution weighting and improves the convergence factor on the basis of traditional algorithms to improve the optimization performance of the algorithm. The proposed method is verified through simulation examples. The results show that the proposed improvement strategy improves the optimization performance of the resource allocation algorithm, effectively improving the system's throughput on limited resources and reducing various channel interferences within the system.